1986
DOI: 10.1002/anie.198609931
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Cl2O6

Abstract: Cl2O6 is present as ionic chloryl perchlorate, ClO 2⊖ClO 4⊖, in the crystalline state. This is not surprising in view of the chemical behavior of Cl2O6–it is used as perchlorate “supplier” for the synthesis of anhydrous perchlorates–but was not to be expected according to the results of earlier structural investigations. The Cl–O distance in the ClO 2⊕ ion (ca. 141 pm) is much shorter than in the neutral ClO2 in the gas phase. Each cation is coupled with two anions (and conversely) to give polymeric groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Due to the shorter Cl−O bonds in comparison to the much longer Cl ⋅ ⋅ ⋅ μ−F interactions, the Cl atom is displaced from the center of the coordination polyhedron. In comparison to previously reported crystal structures of [ClO 2 ] + compounds, such as [ClO 2 ][BF 4 ], [ClO 2 ][RuF 6 ], [ClO 2 ][SbF 6 ], [ClO 2 ][Sb 2 F 11 ], or [ClO 2 ][ClO 4 ], the coordination number of the Cl atom is unexpectedly high [34,39,41,43,44] . Usually, only four short contacts of O or F atoms from surrounding anions are observed.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…Due to the shorter Cl−O bonds in comparison to the much longer Cl ⋅ ⋅ ⋅ μ−F interactions, the Cl atom is displaced from the center of the coordination polyhedron. In comparison to previously reported crystal structures of [ClO 2 ] + compounds, such as [ClO 2 ][BF 4 ], [ClO 2 ][RuF 6 ], [ClO 2 ][SbF 6 ], [ClO 2 ][Sb 2 F 11 ], or [ClO 2 ][ClO 4 ], the coordination number of the Cl atom is unexpectedly high [34,39,41,43,44] . Usually, only four short contacts of O or F atoms from surrounding anions are observed.…”
Section: Resultsmentioning
confidence: 52%
“…The Cl atom of the [ClO 2 ] + cation is always surrounded by additional bridging ligands, either F atoms in fluoridometallate or oxidofluoridometallate salts or O atoms in perchlorate‐containing compounds [37–40] . The coordination number of the Cl atom in the investigated compounds is usually 2+4, with a distorted octahedral arrangement of the ligands, see Table 9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural, spectroscopic and chemical properties of ClO 3 and Cl 2 O 6 have remained controversial over nearly 150 years 47, 8798. Finally, for Cl 2 O 6 , a X‐ray crystallographic analysis of the low temperature solid has confirmed an ionic structure ClO 2 + ClO 4 − ,99, 100 while an IR gas phase and matrix isolation study have suggested a molecular structure of O 2 ClOClO 3 101103. In the gas phase Cl 2 O 6 decomposes rapidly into OClO and O 2 and is not in equilibrium with the anticipated ClO 3 radicals 103.…”
Section: Introductionmentioning
confidence: 99%